Reducing intravenous infusion errors: an observational study of 16 866 patients over five years. (15th February 2018) - Wiseman, Meredith L.; Poole, Susan; Ahlin, Andrea; Dooley, Michael J.
Abstract: Background: Medication administration errors account for the largest proportion of medication errors in hospitals, impacting significantly on patient safety. Intravenous infusions carry a high risk for error due to their complex nature and use in high acuity settings. Two safety strategies for infusion safety introduced across a tertiary hospital network include the utilisation of the clinical pharmacy review and annotation of infusion orders, and the introduction of smart infusion pump technology with dose error reduction software. Aim: The objective of this study was to evaluate the effects of two medication safety strategies: clinical pharmacist review including medication order annotation, and introduction of smart infusion pumps on rate and severity medication administration errors. Method: A pre‐ and post‐intervention, observational study was undertaken at four time points over a five‐year period which included the review of 16 866 patients in a large tertiary referral hospital. Results: Pharmacist annotation independently resulted in a reduction in errors from 16.6 to 8.1%. Subsequent implementation of smart pumps with a comprehensive drug library and high user compliance resulted in a further reduction from 8.1 to 3.9%. These reductions were sustained, with an overall error rate of 5% after two years. Conclusion: The importance of timely clinical pharmacist review of intravenous infusion medication orders, and the implementation of smart infusion pump technology, along with well‐resourced drug library development with emphasis on quality management, education and training, should be prioritised, in order to reduce medication administration errors and to maximise patient safety.